The Implementation of Pancasila Profile to Improve Employment Culture of Vocational High Scholl (SMK) - Wardoyo; Afdal; Hariko, Rezki (Bulletin of Science Education, 2024)
The implementation of the Pancasila Learner Profile Strengthening Project (P5) to improve work culture is a significant effort in shaping the character and career readiness of vocational students in Indonesia. Pancasila, as the nation's founding philosophy, has an important role in guiding learners toward moral, ethical, and professional excellence. This abstract explores the strategies and outcomes of implementing Pancasila profile strengthening in the context of vocational education, specifically focusing on preparing learners for successful employment. Through descriptive research with a qualitative approach, data sources in this study are the Principal, Vice Principal for Curriculum, P5 Coordinator and Grade XII Learners. The research was conducted at one of the SMKs in Central Lampung Regency, the selection of the SMK is an A-accredited school and is one of the Industrial Revolution 4.0 Based SMK Researchers used data collection methods of observation, interviews and documentation obtained from photos, recordings, and other sources from schools. The research also evaluated the impact on learners' character, employability skills and career aspirations. The findings reveal the importance of integrating Pancasila values in work culture and vocational education to foster individuals of good character and morality who are able to contribute positively to society and the world of work.